Profesionalisme Dan Tanggung Jawab Seorang Ilmuwan Dalam Perspektif Islam - Jatri, Intan Safira; Manik, Fransiska Evayanti; Pratama, Friska Surya; Syahidah, Hikmah Haula; Limbangan, Nida Aulia Pangesti; Amrillah, Rizki (Universitas Majalengka, 2023)
People with knowledge have the noblest position because knowledge experts are considered people who continue the struggle of the prophets. Therefore, they must convey and teach their knowledge to humans, to direct them to the path of Allah. Professionalism can be defined as a trait that is reflected in behavior, directed at the goal of carrying out a profession by producing the best quality in the work. A scientist is said to be professional if he can judge what is good and what is bad based on a solid foundation. A scientist has a responsibility to the knowledge he has, whether that knowledge can benefit society or will only cause harm. In this article, we discuss the professionalism and responsibilities of a scientist based on the characteristics of a prophet. This article uses a literature study research method by collecting various quotations from books and journals. The results of the research are the understanding of scientists from an Islamic perspective, the professionalism of a scientist, the prophetic nature that is the basis of a scientist's professionalism, and the responsibilities of a scientist based on religious and state perspectives.